Investigating the behaviour of hybrid fibre-reinforced reactive powder concrete beams after exposure to elevated temperatures - Al-Attar, Alyaa; Abdulrahman, Mazin; Hamada, Hussein Mahmood; Tayeh, Bassam (Elsevier Ltd, 2020)
This study investigated the structural behaviour of reinforced reactive powder concrete (RPC) beams under service load and fire exposure. The beams were composed of hybrid fibres (50% polypropylene fibres and 50% steel fibres) at different volume fractions relative to nonfibrous-reinforced RPC beams. The bottom and both sides of the beams which were simply supported and loaded with two-point loads were exposed to a controlled fire for 120 min in accordance with ASTM E 119 standard time–temperature curve. The midspan deflection was recorded every 5 min. The experiment also included loading tests on fire-damaged beams after cooling. The nonfibrous-reinforced RPC beams failed during the fire test after 38 min because of the spalling of the reinforcement cover which directly exposed the reinforcing steel to elevated temperatures. By contrast, the beams with hybrid fibres could resist failure during the entire test period. The rate of increase in deflection during fire exposure declined with an increase in hybrid fibre content. Increases in fibre volume fraction from 0.25% to 0.75% and 1.25% decreased the midspan deflection of the reinforced RPC beams by 33% and 36%, respectively. Adding hybrid fibres could considerably improve the residual stiffness of fire-damaged beams.